Akulturasi Budaya Jawa dengan Budaya Islam pada Bulan Muharram di Desa Brayo Wonotunggal Kabupaten Batang - Maya Ika Trisnawati; Hana Dian Malasari; Alvian Varihul Mustavid; Ahmad Noor Afifuddin; Muhammad Nadhiful Hakim; Pradipta Kurniasanti (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Nyadran is a series of traditional ceremonies, which are part of cultural heritage and believe that certain places are sacred or holy places. Nyadran traditions like this are a from of salvation carried out as a from of gratitude and respect for ancestors. The data collection technique used in this research was interviews with the main sources, the head of the Nyadran committee and the of Brayo village. The location of this research was in Ujung Biru Hamlet, Brayo Village, Wonotunggal District. Nyadran activities in Ujung Biru Hamlet are held in the month of Muharrom because Muharrom is not the Hijri New Year. Nyadran implementation in Brayo Village has been carried out since ancient times, as time goes by, the nyadran tradition has undergone many changes